Separation of the equations of motion in two-dimentional gravitatrional pendulums - Lavcel-Budko, Olga; Krylovas, Aleksandras; Miškinis, Paulius (Lietuvos matematikos rinkinys, 2012)
We solve the classical problem-model of the oscillation of the gravitational pendulum on the elastic thread. This task was formulated, but it is not completely solved in the classical K. Magnus monograph “Wavering”. With additional assumptions about the analyzed model in question (mass conservation law and considerations about certain physic) system of the differential equations of the two second-order nonlinear oscillation transformed into a third order nonlinear differential equation which is solved numerical approximate using the Maple program. The solution is compared with asymptotic in a long time range.